2022
DOI: 10.1007/s10462-022-10285-3
|View full text |Cite
|
Sign up to set email alerts
|

An overview of violence detection techniques: current challenges and future directions

Abstract: The Big Video Data generated in today's smart cities has raised concerns from its purposeful usage perspective, where surveillance cameras, among many others are the most prominent resources to contribute to the huge volumes of data, making its automated analysis a difficult task in terms of computation and preciseness. Violence Detection (VD), broadly plunging under Action and Activity recognition domain, is used to analyze Big Video data for anomalous actions incurred due to humans. The VD literature is trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…According to a recent study by Mumtaz et al [ 46 ], the main studies for recognizing violent human actions contain little information about efficiency results, i.e., information about the complexity and number of parameters, confirming that their objective was to find good results in terms of accuracy while increasing the complexity of the model. It was shown that proposals based on optical flow, 3D CNN, LSTM, two-stream networks, and 3D skeletons have high computational costs and cannot be used in real-time scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…According to a recent study by Mumtaz et al [ 46 ], the main studies for recognizing violent human actions contain little information about efficiency results, i.e., information about the complexity and number of parameters, confirming that their objective was to find good results in terms of accuracy while increasing the complexity of the model. It was shown that proposals based on optical flow, 3D CNN, LSTM, two-stream networks, and 3D skeletons have high computational costs and cannot be used in real-time scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…CNN and Sequence Models [39] They can have good classification accuracy and can be computationally light depending on the number of layers used. They also can adapt to new data.…”
Section: Reference(s) Strengths Weaknessesmentioning
confidence: 99%
“…Automatic Violence Detection and Classification (AVDC) of video content has recently emerged as a critical problem [1,2], leading to an increased focus on using Deep Learning (DL), computer vision, and image processing methods for flagging unsuitable content and detecting violent behaviour [3]. Automatic and real-time video analysis is imperative to identifying violent offenders and maintaining the safety of cities [4,5].…”
Section: Introductionmentioning
confidence: 99%